Outcome of Hemispherectomy in Sturge-Weber Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
A questionnaire was mailed to the parents of 70 patients identified by the Sturge-Weber Foundation as recipients of hemispherectomy between 1979 and 2001, and responses obtained from 32 (46%) were analysed at the Johns Hopkins Hospital, Baltimore, MD.